Effect of “LeHeR maneuver”on glottic view as assessed with POGO score during video laryngoscopy - Sunil Rajan; Jacob Mathew; Gayathri Sreekumar; Lokeshshiva Arul; Kajol N. Amin; Jerry Paul (Journal of Anaesthesiology Clinical Pharmacology, 2025)
Background and Aims: Left head rotation maneuver improves the glottic view during direct laryngoscopy. We assessed whether rotating the head to the left side to 45° in supine position improves the glottic view as assessed with the percentage of glottic opening (POGO) score during video laryngoscopy compared to sniffing position. Ease of intubation, time to intubate, and hemodynamic changes were also assessed. Material and Methods: This prospective, observational study was conducted in 41 patients with difficult airway requiring video laryngoscope–aided nasotracheal intubation. Following intravenous induction and neuromuscular blockade, indirect laryngoscopy was attempted with C-MAC videolaryngoscope with the patient’s head in sniffing position. Best glottic view was graded as per the POGO scoring system. In patients having partial or no glottic view, patient’s head was rotated to the left side to 45° and the best glottic view was obtained and scored. Intubation was attempted in this position, and ease of intubation was documented. Results: Majority of patients showed improvement of >25% POGO score following left head rotation compared to sniffing position (85.37% vs. 14.63%). Significantly higher number of patients in sniffing position had a POGO score of 0–25%, while it was >50–100% in left head rotation position. Median POGO score was significantly higher in left lateral position compared to sniffing position (75% vs. 25%). Intubation was easy in 69.29% of patients. There was no significant change in hemodynamic parameters during intubation. Conclusion: Rotating the head to the left side to 45° in supine position improved the glottic view during indirect laryngoscopy using C-MAC videolaryngoscope compared to sniffing position.